On the Constitutionalization of Chinese Citizens’ Environmental Rights - Liu, Xinyue (Transactions on Social Science, Education and Humanities Research, 2024)
The citizen’s environmental right is an important part of the modern legal system. It aims at protecting the basic rights and interests of citizens, promoting environmental protection and sustainable development. The right needs to be effectively guaranteed and implemented through laws, policies and social actions. Environmental rights have been gradually accepted by all countries in the world. Although the idea of environmental rights into the constitution has a long history, it has a different era significance in the present. The construction of a beautiful new China and a beautiful new world requires the promotion and protection of environmental rights in the Constitution. In the new era, China still faces severe ecological and environmental problems at home and abroad. In order to effectively solve the environmental problems facing China, fulfill the state responsibility for environmental protection and the task of The Times for environmental governance, the Constitution should stipulate citizens’ environmental rights.